Targeting phosphodiesterase 5 as a therapeutic option against myocardial ischaemia/reperfusion injury and for treating heart failure - Korkmaz-İçöz, Sevil; Radovits, Tamás; Szabó, Gábor (British journal of pharmacology, 2018)
Phosphodiesterase type 5 (PDE5) selectively hydrolyses the second messenger cGMP into 5′-GMP, thereby regulating its intracellular concentrations. Dysregulation of the cGMP-dependent pathway plays a significant role in various cardiovascular diseases. Therefore, its modulation by drugs, such as PDE5 inhibitors, may represent an effective therapeutic approach. There are currently four PDE5 inhibitors available for the treatment of erectile dysfunction: sildenafil, vardenafil, tadalafil and avanafil. Sildenafil and tadalafil have also received Food and Drug Administration approval for the treatment of pulmonary arterial hypertension. This review summarizes the pharmacological aspects and clinical potential of PDE5 inhibition for the treatment of myocardial ischaemia/reperfusion injury and heart failure. Linked Articles This article is part of a themed section on Inventing New Therapies Without Reinventing the Wheel: The Power of Drug Repurposing. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.2/issuetoc
First published: 18 February 2017
Gesehen am 24.10.2018